2010
DOI: 10.1111/j.1365-2672.2010.04785.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus endospore resistance to gas dynamic heating

Abstract: Aim:  To develop a novel laboratory procedure for the study of shock wave‐induced damage to Bacillus endospores. Methods and Results:  Bacillus atrophaeus endospores are nebulized into an aerosol, loaded into the stanford aerosol shock tube and subjected to shock waves of controlled strength. Endospores experience uniform test temperatures between 500 and 1000 K and pressures ranging from 2 to 7 atm, for a relatively short time (2–3 ms). During this process, the bioaerosol is observed using in situ laser absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 14 publications
3
20
1
Order By: Relevance
“…We also assessed the accuracy of our temperature measurements and the distribution of heat along the length of the wire by using blackbody calibration, which showed that the wire temperature measurement fit to theoretical values precisely, especially below 1000°C. Unlike the reported temperature measurements using thermocouples in the gas-phase spore inactivation studies that show a certain spatial temperature distribution [17][18][19][20][21][22][23][24][25], our results show a narrow temperature distribution along the entire length of the wire (see the evenly distributed temporal light intensity on wire in Fig. S4).…”
Section: Temperature Profiles Of Bs Spores On the Pt Wire Surfacecontrasting
confidence: 84%
See 2 more Smart Citations
“…We also assessed the accuracy of our temperature measurements and the distribution of heat along the length of the wire by using blackbody calibration, which showed that the wire temperature measurement fit to theoretical values precisely, especially below 1000°C. Unlike the reported temperature measurements using thermocouples in the gas-phase spore inactivation studies that show a certain spatial temperature distribution [17][18][19][20][21][22][23][24][25], our results show a narrow temperature distribution along the entire length of the wire (see the evenly distributed temporal light intensity on wire in Fig. S4).…”
Section: Temperature Profiles Of Bs Spores On the Pt Wire Surfacecontrasting
confidence: 84%
“…3B). Together, our results indicate that surface attached spores heated in our fast heating scheme ($10 4°C /s) behave similar to dry spores heated in other aerosol heating schemes [17][18][19][20][21][22][23][24][25].…”
Section: Spore Inactivation At Fast Heating Rates ($10 4°c /S) Througsupporting
confidence: 52%
See 1 more Smart Citation
“…To summarize the above review, two separate techniques have generally been employed to confine a gas mixture to part of a shock tube: a ball valve [11][12][13] and a gate valve [14][15][16][17] (note that the use of thin diaphragms for gas separation in shock tube driven sections 18 is uncommon because the diaphragm fragments created as the incident shock wave shatters the diaphragm interfere with diagnostics located in the test section). Of the two techniques, we consider the gate valve to be superior for our application because it is thinner and occupies less volume than a ball valve (particularly for our relatively large 11.53-cm diameter tube).…”
Section: B Previous Researchmentioning
confidence: 99%
“…In that work, the buffer gas was chosen to be the same as that of the test gas but with no fuel aerosol droplets, and the gate valve was located approximately 1.2 m from the shock tube 17 who employed it to confine a post-reflected-shock gas/endospore aerosol mixture after expansion wave-induced cooling in order to collect samples of biological aerosols. The technique used by Gates et al is similar to that used in single pulse shock tubes, 11-13 except a sliding gate valve was used instead of a ball valve.…”
Section: B Previous Researchmentioning
confidence: 99%